THE EFFECT OF USE MODEL MAKE A MATCH & PICTURE AND PICTURE AND STUDY LEARNING STYLE ON LEARNING RESULTS OF SOCIAL KNOWLEDGE CLASS II CLUSTER XI CIBINONG-BOGOR - ajat sudrajat; Marfuah Darojat (Journal Civics and Social Studies, 2020)
This research is a quantitative research that aims to know the difference of learning result of Social Knowledge learners using learning model make a match and picture and picture; Differences in learning outcomes of Social Knowledge learners who have a tendency of visual, auditorial, and kinesthetic learning styles; And the influence of interaction between cooperative learning model and student learning style tendency toward Social Knowledge learning result. The research was conducted in Cibinong District XI Cluster with sample of students of class II of SDN Ciriung 02 ( Public School Ciriung 2) which amounted to 78 students. Instrument used in this research is questionnaire and test result of learning. Data analysis techniques in this study using Saphiro Wilk Test to test the normality of data and Bartlett Test to test the homogeneity of data. After that, two way analysis of variance (ANOVA) Test was done to test the difference of mean value between groups followed by Tukey HSD test to see group interaction with reference to significant level α = 0,05. The results showed that there was a difference between learning outcomes of IPS learners using cooperative learning model make a match and picture and picture with significance of 0,000; There are differences in learning outcomes of Social Knowledge learners who have a tendency of visual, auditorial, and kinesthetic learning styles with significance of 0,001; And there is no direct interaction effect between the use of cooperative learning model and the learner's learning style tendency toward Social Knowledge learning result. This is indicated by a significance of 0,535.Keywords : Make a Match, Picture and Picture, learning style, Social Science learning result.